E-ZAKAT: AN APPROACH FOR ZAKAT MANAGEMENT TO ERADICATE POVERTY - Rouf, Md. Abdur; Rony, Jahid Hasan; Karim, Nazmul; Bhuyan, Md Fahim; Begum, Momotaz (International Journal of Islamic Banking and Finance Research, 2021)
This paper has shown an online-based zakat management system named E-ZAKAT. Zakat is one of the main foundational goals of the world’s second-largest religion, Islam. So, it has indisputable importance for a country as well as the world economy and poverty eradication. During the COVID-19 pandemic, people have become habituated with the online system due to unavoidable situations, such as education and commodity market has now turned into online systems. However, an online base zakat management system for both donors and seekers has not prevailed widely. Here in this proposed system, the donor can calculate, donate their zakat, and the seeker can apply to receive it. Instead of providing cash, business or agricultural help is planned to ensure the economic stability of a low-income family. For this purpose, the expectant can claim support for green farming, agricultural equipment, or money to start a small business after ensuring the required verification and qualification steps. The proposed dynamic web application E-ZAKAT will provide an easier and hassle-free system for zakat donors and seekers with an attractive design. As a result, proper utilization of our system could provide a positive impact to change our society as well as our world. JEL Classification Codes: I3, N3, P36, P46, H3.